An Unknown Ivory Carver from the Treasury of the Zagreb Cathedral - Milinović, Dino (Array, 2013)
Four ivory plaques kept in the Zagreb Cathedral Treasury are the only original parts of the ivory plenarium, mentioned in the oldest existent inventory of the Treasury: plenarium in quo est nativitas Christi sculpta in ebore. The 1425 inventory mentions other scenes (cum aliis historiis in ebore) in addition to Nativity. The original frame, described in detail in the 1394 inventory has not been preserved.